1999
DOI: 10.1111/j.1365-2621.1999.tb09869.x
|View full text |Cite
|
Sign up to set email alerts
|

Textural Properties of Raw Salmon Fillets as Related to Sampling Method

Abstract: Textural properties of raw Atlantic salmon (Salmo salar) fillets from different origin were studied on different locations of the fillets. Three instrumental methods were applied for evaluation of textural properties. Two methods were based on puncture tests, using flat-ended cylinder or spherical probes measuring the hardness of the fillet. The third method was based on cutting the fillet with a blade and measuring the shear force. Hardness and shear force increased from head to tail, and the location below t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
100
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(118 citation statements)
references
References 13 publications
12
100
0
2
Order By: Relevance
“…The results of Alasalvar et al (2001) supported our findings for their study relating to the shelf life of gilt head sea bream. Sigurgisladottir et al (1999) studied the textural properties of raw salmon fillets and also found similar results.…”
Section: Color and Texture Characteristics Resultssupporting
confidence: 55%
“…The results of Alasalvar et al (2001) supported our findings for their study relating to the shelf life of gilt head sea bream. Sigurgisladottir et al (1999) studied the textural properties of raw salmon fillets and also found similar results.…”
Section: Color and Texture Characteristics Resultssupporting
confidence: 55%
“…The Instrumental Texture (TI) was measured by a QTS Texture Analyzer (Brookfield) and determined the firmness (consistency) parameter according to Sigurgisladottir et al (1999) with the following analysis parameters: ambient temperature; compression force measure (N), testing velocity: 2.0mm s -1 ; trigger point: 0.1 N; distance: 214mm; target value: 20 N; and probe: 70 x 3mm single blade. The fillets were cut into 2 x 2 x 1.5cm pieces for this analysis.…”
Section: Adult Tambaqui (Colossoma Macropomum)mentioning
confidence: 99%
“…Fig. 3a shows that hardness increased 300 %; from 400 to 1600 g. Sigurgisladottir et al (1999) found that hardness of Atlantic salmon net from the freezer, in a single layer. The tip of the probe needle was placed into the geometric center of one fresh fillet.…”
Section: Resultsmentioning
confidence: 99%